SOCIOLOGICAL CLASSIFICATION AND FACTORS OF ENTREPRENEURSHIP SUPPORT IN INTERNATIONAL PRACTICE - Kozokov Sobirjon Zokirjonovich (Western European Studies, 2024)
The article analyzes the sociological factors of supporting entrepreneurial activity in developed countries of the world. The author investigated the socioeconomic trends of entrepreneurship in the United States, Japan and Germany in the context of objective reasons for government support for entrepreneurship, opportunities created by them, and ongoing reforms. It also outlines the factors that contribute to the well-being of the developed countries as a result of the development of entrepreneurship worldwide in the 70-80s of the 20th century.
Keywords: Entrepreneurship; Social Change; Employment; State Program